Planting flags in water - Koch, Natalie (Dialogues in human geography, 2022)
In this commentary, I respond to James Riding and Carl Dahlman's article, ?Montage space: borderlands, micronations, terra nullius, and the imperialism of the geographical imagination?. I build on their arguments about ?more-than-dry landscapes? to consider how the relationship between fluid and non-fluid landscapes sheds light on the construction and contestation of political space. To do so, I offer additional examples of how people plant flags in water, shedding light on the political implications of how physical territories are imagined, claimed, and sometimes, simply created at the fluid/non-fluid interface.
Gesehen am 05.12.2022